PENGARUH BIAYA DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA PT. SINAR NIAGA SEJAHTERA CABANG MEDAN - Eko Prasetyo (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2020)
This study discusses the distribution of costs to sales volume at PT. Sinar Niaga Sejahtera Medan branch. Based on the type of data, this research is a quantitative study because the data used is numeric. PT. Sinar Niaga Sejahtera Medan. The sample in this study is the monthly income statement of PT. Sinar Niaga Sejatera Medan branch from 2016-2018 (12 months x 3 years = 36) so that the observation data obtained get 36 samples. Based on the t test, the tcount was found to be 8,919 with a significance level of 0,000. While the value of ttable is 1.69092. Because the value of tcount (8.919)> ttable (1.69092) and the significance value of 0.000 <0.05, H0 is rejected and Ha can be accepted as a significant distribution cost to the sales volume of PT. Sinar Niaga Sejahtera Medan. The coefficient of determination test results (R2) obtained R Square value of 0.701 or equal to 70.1%, concluded that it concerns the distribution costs of the sales volume of PT. Sinar Niaga Sejahtera Medan was 70.1%, while the remaining 29.9% was accepted by other variables through this research.